PENGEMBANGAN KREATIVITAS ANAK USIA DINI MELALUI METODE PEMBELAJARAN FIELD TRIP DI TK RAHMATKAN KOTA JAMBI: creativity development, early childhood, learning methods, field trip. - Nurul Annisa Dewantari Nasution; Yulianti Yulianti (Prodi PIAUD, Fakultas Tarbiyah dan Keguruan, UIN Sulthan Thaha Saifuddin Jambi, 2020)
This study aims to determine the application of learning methods through field trips to increase the creativity of early childhood in kindergarten of Rahmatkan, Jambi city. The research method used is descriptive qualitative. Data obtained from the results of interviews, observations and documentation sourced from kindergarten of Rahmatkan, Jambi city. The data collected was followed up with data reduction, data display and drawing conclusions. Kindergarten or kindergarten was established as an effort to develop all aspects of the personality of students in order to bridge family education to school education. The scope of the program of learning activities includes; the formation of behavior through habituation in the development of Pancasila moral, religion, discipline, social emotional, and social skills, as well as the development of basic abilities through activities prepared by the teacher including developing language skills, thinking power, creativity, skills and physicality. The field trip learning method is able to stimulate creativity which makes children more confident, daring to appear and dare to try new things that stimulate high curiosity as a creative characteristic.